Exploring Self-Regulation of Patients with Chronic Kidney Disease Undergoing Hemodialysis - Belinda Belinda; Zahrasari Lukita Dewi (Jurnal Psikologi, 2021)
Patients with chronic kidney disease (CKD) undergoing hemodialysis often experience residual impacts of the treatment on their physical, economic, social, and psychological, to an extent that CKD is considered a barrier for individuals to fully participate and enjoy life. It is crucial for CKD patients self-regulate their cognitive, social and emotional health in order to function optimally. This research aimed to explore the self-regulation process of CKD patients. This research adopted a qualitative exploratory utilizing in-depth interview as a data collection technique. There were three participants in the research recruited through convenience sampling, two men and one female aged 50-60 years and undergoing hemodialysis within 6-10 months.  The analysis process used thematic analysis guided by a common-sense model of self-regulation. Findings showed that at an initial stage patients perceived CKD and its treatment emotionally, but this was changed over time to be more positive. Two participants had adequate coping strategies and received support from the closest relatives to assist in the evaluation, while, one participant was more emotionally harboring and lacked social support. The evaluation process could encourage participants to seek information and understand CKD better. Further research suggested that sampling techniques could involve participants with a more diverse age range in order to have more varied data that can be used by other CKD patients with diverse age range.